Paul Strand - Strand, Paul 1890-1976 (Aperture masters of photography, 2014)
Paul Strand (born in New York, 1890; died in Orgeval, France, 1976) is one of photography's great modernist masters. Alongside Edward Weston and Alfred Stieglitz, he pushed the artistic potential of the medium to new heights. Strand's long career began as a student of Lewis Hine, and by 1917, he was already recognized as an important artist; the last issue of Stieglitz's Camera Work magazine was entirely devoted to his photographs, including many of his early masterpieces. After broadly exploring the modernist possibilities of photography and filmmaking, Strand moved to Mexico in 1932, where his work began to reflect his ambition to make comprehensive portraits of places. Thereafter, he made photo-essays about different regions around the world, staying for extended periods in the Hebrides in Scotland, Egypt, Morocco, France, Italy, and Ghana, among other places; each body of work is composed of portraits, landscapes, and architectural details. Strand's life's work is the subject of a major touring retrospective, curated by Peter Barberie, beginning at the Philadelphia Museum of Art in 2014